ANALISIS PERBANDINGAN KINERJA INDEKS SAHAM SYARIAH DAN KINERJA INDEKS SAHAM KONVENSIONAL - DWI LESTARI, RIZKI (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: This research was conducted with the purpose of find out and analyzing the Jakarta Islamic Index comparison with LQ45 indices in Indonesian Stock Exchange (IDX) with risk adjusted performance measurement methods. Determination of the sample using purposive sampling technique. The data used is secondary data based publications Indonesian Stock Exchange (IDX). Data were obtained based on the criteria that the stock price index every month Jakarta Islamic Index and LQ45 stock price index by using descriptive analysis. Performance measurement using risk adjusted performance against the Jakarta Islamic Index and LQ45 through the Sharpe index, Treynor index, Jensen index. The results show that the performance of the Jakarta Islamic Index better than performance LQ45in the year 2008,2009,2012. Jakarta Islamic Index worse than the performance LQ45 in the year 2010,2011. Shows that the overall performance of the Jakarta Islamic Index is better than performance LQ45 because a screening conducted Indonesia Stock Exchange on the Jakarta Islamic Index produce good performance when economic conditions decline. Screening process conducted on the Indonesia Stock Exchange to LQ45 produce better performance than Jakarta Islamic Index in normal economic conditions. Keywords: performance index of stock prices, risk and return, risk adjustedperformance